2021
DOI: 10.1093/brain/awab225
|View full text |Cite
|
Sign up to set email alerts
|

Six-dimensional dynamic tractography atlas of language connectivity in the developing brain

Abstract: During a verbal conversation, our brain moves through a series of complex linguistic processing stages: sound decoding, semantic comprehension, retrieval of semantically coherent words, and overt production of speech outputs. Each process is thought to be supported by a network consisting of local and long-range connections bridging between major cortical areas. Both temporal and extratemporal lobe regions have functional compartments responsible for distinct language domains, including the perception and prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 116 publications
2
53
0
Order By: Relevance
“…49 Nonetheless, we have recently demonstrated that the velocity of SPES-induced neural propagations was highly comparable between the opensource and individual DWI data. 35 One should consider the effect of volume conduction when electrode sites >10 mm apart exhibit an identical waveform without a time delay. 50 Based on the visual assessment, we believe that the unwanted effect of volume conduction on our iEEG analysis was small.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…49 Nonetheless, we have recently demonstrated that the velocity of SPES-induced neural propagations was highly comparable between the opensource and individual DWI data. 35 One should consider the effect of volume conduction when electrode sites >10 mm apart exhibit an identical waveform without a time delay. 50 Based on the visual assessment, we believe that the unwanted effect of volume conduction on our iEEG analysis was small.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…As previously performed, 14,35 we generated DWI tractography using the open‐source data averaged across the 1065 individuals participating in the Human Connectome Project (http://brain.labsolver.org/diffusion-mri-templates/hcp-842-hcp-1021). 36 We validated our analytic approach by demonstrating that the spatial patterns of SPES‐induced neural propagations based on the open‐source DWI data were similar to those based on the individual data 35 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the various iEEG frequency bands ranging from alpha through high-gamma, event-related high-gamma augmentation was reported to best predict the severity of cognitive deficits following focal brain resection ( Sonoda et al, 2022 ). Diffusion-weighted imaging (DWI) tractography can visualize the direct white matter tracts allowing neural communications between distant cortical regions concurrently involved in a cognitive process ( Sonoda et al, 2021 ). The present study elucidated the spatiotemporal dynamics and functional significance of iEEG-derived neural modulations during task switching by addressing the following aims.…”
Section: Introductionmentioning
confidence: 99%
“…We performed this analysis to provide the biological plausibility for direct functional connectivity between distant cortical areas concurrently involved in task switching. It is suggested that cognitive processes are supported by spatially-distinct, simultaneous high-frequency neural events generated by monosynaptically connected cortical networks ( Singer, 1993 , 2018 ; Buonomano and Merzenich, 1998 ; Sonoda et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%